Prevalence of sensory peripheral neuropathy in diabetic patients at diabetes care centre: a cross sectional study - Battula, Pradeep; Afreen, S.; Meena, E.; Reddy, S. Siva Ram; Sujatha, G. (International Journal of Research in Medical Sciences, 2017)
Background: Diabetic neuropathy is a nerve damaging disorder associated with diabetes; result from micro vascular injury involving small blood vessels that supply to the nerve (vas nervorum) in addition to macro vascular condition that can culminate in diabetic neuropathy. By the year 2025 hundreds of people were estimated to become diabetic. The rates of prevalence of neuropathy increasing worldwide which is directly related to the nonmodifiable risks like age, duration of diabetes, obesity, alcoholism, gender. Methods: A cross sectional interventional study was conducted on diabetic patients. Questionnaire, instruments and demographic details were used to collect data from patients. The diabetic neuropathy is conformed in patients by using biothesiometric analysis, tuning fork, monofilament, NSS and NDS. Results: Total 331 subjects included in the study, 200 cases diagnosed with DPN according to biothesiometry and prevalence percentage was found to be 60.4% and incidence was found to be 8.76% respectively. A significant greater proportion of males reported neuropathy more than females. The association between the obesity and the DPN was (r2=0.7922) low positive correlation. High positive correlation was confirmed with NSS, NDS respectively. Conclusions: It was concluded that there is a higher prevalence (60.4%) and incidence (8.76%) of neuropathy among the diabetic subjects and it may go on increasing as the age progress.